Hepatic foreign body removal with intravascular occlusion balloon in retrohepatic IVC in a pediatric patient - Daniel B. Gehle; Ying Z. Weatherall; Sara A. Mansfield; Erica L. Mitchell; Howard I. Pryor, II (Elsevier, 2022)
Penetrating hepatic injuries in pediatric patients represent a clinical challenge that carries significant morbidity and mortality. We report a case of a 13-year-old male with a penetrating injury to his right flank that resulted in a diaphragmatic injury, liver laceration, and a retained hepatic foreign body nearly abutting a major vessel. We review the literature on managing penetrating hepatic injuries in pediatric patients and describe our novel hybrid endovascular approach for hepatic vascular isolation during open intrahepatic foreign body removal.